Impact of Demographic variables and Risk Tolerance on Investment Decisions – An Empirical Analysis - Kavita Chavali; M. Prasanna Mohanraj (International Journal of Economics and Financial Issues, 2016)
This empirical study explores the investment pattern and financial decision making of individuals and their risk tolerance. The study has adopted financial risk tolerance scale proposed by Grable and Lytton to measure the different dimensions of financial risk.  Kendall's W Test is used to ascertain the preferred source of investment of individuals. Chi square test is used to determine the demographic variables and their relationship with investment pattern. The study reveals that gender has an impact on the investment pattern and decision making of respondents.